Komik Strip Sebagai Sarana Kritik Sosial - Mubarok, Muchammad Bilal; Fakruroji, Moch; Tresnawaty, Betty (Annaba: Jurnal Ilmu Jurnalistik, 2021)
This study aims to provide an overview of the three signs in comics that discuss the topic of social criticism, while the signs are representamen, object and interpretant. The study method used is semiotics initiated by Charles Sanders Peirce, while the concept states that in carrying out an identification it is necessary to look at a sign such as a representamen, object and interpretant. The results of the study show that the Faktap Comics Instagram account can be used as a social control tool on the grounds that the Faktap Comics Instagram account is a social media that can provide important information and contains messages of social criticism in every post. Social criticism is an important part of a control that exists in society.